Transforming rice straw into eco-friendly growing medium for microgreens: a solution for agricultural waste management - Saurabh, Kirti; Roy, Himadri Shekhar; Shubha, Kumari; Sundaram, Prem Kumar; Prakash, Ved; Koley, Tanmay Kumar; Mukherjee, Anirban; Sarkar, Bikash; Singh, Anil Kumar; Das, Anup; Upadhyaya, Ashutosh; Jeet, Pawan; et al. (Frontiers in Sustainable Food Systems, 2025)
IntroductionRice straw burning is a major environmental concern in India, contributing to severe air pollution and climate change. Sustainable alternatives for its utilization are essential to mitigate these issues. One promising approach is repurposing rice straw as a growing medium for microgreens, addressing both agricultural waste management and the need for sustainable substrates. This study evaluates the feasibility of using pretreated rice straw as a substrate for microgreen cultivation and compares its performance with conventional substrates like cocopeat and vermiculite.MethodsRice straw was pretreated with sodium hydroxide (NaOH) at varying concentrations (1%–7%) to improve its physicochemical properties. Changes in ash content, water holding capacity (WHC), and suitability as a growing medium were assessed. Microgreens of amaranth, cabbage, and cauliflower were cultivated on pretreated rice straw, cocopeat, and vermiculite. Growth parameters, including plant length and fresh weight, were recorded. Additionally, the micronutrient content (Fe, Zn, Mn) of plants grown in different substrates was analyzed. Principal Component Analysis (PCA) was conducted to identify key factors influencing plant growth and nutrient uptake.ResultsNaOH pretreatment significantly improved the quality of rice straw, reducing ash content from 20.05% (untreated) to 7.10%–11.10% and increasing WHC to 673%, which was comparable to cocopeat (891%) and superior to vermiculite (389%). Among the microgreens tested, cabbage achieved the highest plant length (6.2 cm) and fresh weight (59.83 mg plant−1) when grown on rice straw. While vermiculite supported higher levels of essential micronutrients, including Fe, Zn, and Mn, rice straw demonstrated remarkable performance in plant growth and biomass production. PCA revealed that rice straw was positively associated with plant weight and length, whereas vermiculite correlated with micronutrient accumulation.DiscussionThe findings highlight the potential of pretreated rice straw as an effective alternative to conventional growing media. Despite vermiculite providing higher micronutrient availability, rice straw supported robust plant growth, making it a viable substrate for microgreen cultivation. Further fortification of rice straw could enhance its nutrient-holding capacity, making it even more comparable to existing commercial substrates. This study demonstrates that utilizing rice straw as a growing medium offers an eco-friendly, cost-effective solution for sustainable agriculture while reducing environmental pollution caused by straw burning.